Flexible Implementation of Technological Innovations in Polish Industrial Companies - Magdalena K. WYRWICKA; Beata MRUGALSKA (Communications of International Proceedings, 2021)
Technological innovations are perceived as a critical mechanism which can assure a secure position in the competitive world of the future. However, the level of their implementation still differs among countries even in the UE member states. This paper attempts to propose a system supporting planning procedure to gradual and flexible introduction of technological innovations. In order to achieve it, constrains from the market, production system and development strategy are determined. A set of uncertainties relating to economic situation, position on the market and characteristics of the company including stages of life cycle and organizational balance, is also described. The proposal is supported empirically as case studies are performed on a sample of technology companies in the Wielkopolska region in Poland.
Keywords: Flexible Implementation; Innovation; Organizational Balance; Technological Innovation.